Body dissatisfaction in university women: new psychometric evidence from the 14-item Body Shape Questionnaire (BSQ-14) [Insatisfacción corporal en mujeres universitarias: nuevas evidencias psicométricas del Body Shape Questionnaire de 14 ítems (BSQ-14)] - Izquierdo-Cárdenas, S. (2021)
ABSTRACT In recent years, young university students have experienced a greater concern for the body aspect that is related to having a slim figure. In this sense, it is important to have tools to measure the dissatisfaction they may have with their body appearance. The objective of the study was to evaluate the psychometric properties of the Body Shape Questionnaire (BSQ-14). Specifically, to evaluate the internal structure of the BSQ-14, the internal consistency of the model, the evidence of discriminant validity based on the correlations of the average score of the BSQ-14 with a measure of mindfulness and the invariance of the BSQ-14 model, considering the variable of performance of physical activities. For hundred two young university students from Metropolitan Lima participated, with an average age of 20.05 years (SD = 18.18). A test battery including the BSQ-14 and Mindful Attention Awareness Scale (MASS-5) was administered. The results indicate that the one-dimensional structure of the BSQ-14 presented a good fit (χ² = 571,420; CFI = 0.962; SRMR = 0.051) and adequate reliability by the internal consistency method (ω = 0.962). Likewise, the BSQ-14 showed negative correlations with Mindfulness and body satisfaction. The BSQ-14 was shown to be invariant among university women who do or do not exercise. It is concluded that the study provides results that support the use of the BSQ-14 to measure body dissatisfaction with evidence of validity and reliability in a sample of young university students. of Metropolitan Lima.